Feasibility of Investment in Tourism Villages Towards Sustainable Development: A Comparative-Phenomenology Study - Noviriani, Eliza; Ee Zurmansyah (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
This applied research is a development of previous research, namely the study of the business feasibility of the Jawai Laut tourist village in Sambas Regency, West Kalimantan. The researcher expanded the study by conducting a comparative study of the phenomenological approach to explore the feasibility of investment in two tourist villages in Sambas Regency, West Kalimantan, namely the Jawai Laut and the Piantus Tourist Village. This is to answer the challenges of the novelty of research exploration and support village digitalization for sustainable village economic development. The method used is a combination of the comparative-phenomenological approach. Exploration shows The Jawai Laut Tourist Village meets the investment feasibility criteria for three financial ratios, namely Payback Period (PP), Average Rate of Return (ARR), and Net Present Value (NPV). Meanwhile, the Piantus Tourist Village meets the investment feasibility criteria for two financial ratios: the Average Rate of Return (ARR) and Net Present Value (NPV). Despite some shortcomings, the financial analysis shows that investment in the two tourist villages is feasible. Investors can consider the existence of a promising projection of tourist village income in the future. This reality proves that village communities can manage their regional potential independently without eliminating their region's uniqueness.